Creation in the Old Testament - William P. Brown (St Andrews Encyclopaedia of Theology, 2022)
Creation in the Old Testament (or Hebrew Bible) is not limited to the first two creation accounts in Genesis (1:1–2:3; 2:4b–3:24). It is a widespread theme featured not only in Genesis but also in the Psalms, the Prophets, and the Wisdom literature. This article surveys representative creation texts in the Old Testament, noting their particularities and differences as well as exploring their theological and ecological relevance for contemporary communities.